Evaluation of paste technology to co-dispose of ash and brines at Sasol synfuels complex - Mahlaba, Samuel Jabulani (My University, 2008)
ABSTRACT There is currently a ubiquitous drive for South African industries to improve on water usage as large volumes of raw water are consumed and saline effluents (brines) are produced during their operations. This dissertation addresses the use of paste technology to co-dispose brines as well as solid wastes, from the SASOL Secunda complex in a sustainable manner. The findings from this study indicated that the properties of pastes with relatively high solids concentrations (e.g. 70%) are dependent on the physical properties of fly ash, such as carbon content and fineness thus impacting on the transportability of the paste. In order to overcome this effect, the paste with a 65% solids concentration will be less sensitive to the physical properties of the fly ash. Furthermore the chemical composition and salt load of brines affect the transportability and salt retention of paste. It was also observed that salinity of the brine affects the settling rate of the paste. The availability of various brines at SASOL provides an opportunity to investigate the blends of brines that will provide suitable settling and salt retention of paste. The other opportunity identified was the use of SASOL solid wastes such as incineration ash (IA) and gasification ash as additives to improve paste properties. It was also discovered that the mode of salt retention is predominantly chemical rather than physical, which increases the credibility of this technology. The overall conclusion is that paste technology is a potential solution for sustainable co-disposal of ash and brines. Further research areas are proposed to improve the understanding of paste technology and its implementation.
Keywords: paste technology; ash; brines; SASOL